2021
DOI: 10.1029/2021gl094015
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Magnetosonic Waves in the Slot Region Observed by Van Allen Probes

Abstract: The slot region, normally located at L = 1.8-3.0 and separating the Earth's inner and outer radiation belts, can be highly dynamic during geomagnetically disturbed periods (Lyons & Thorne, 1973;Meredith et al., 2007). Many previous studies have focused on various physical processes including the evolution of pitch angle distributions (PADs) (Zhao et al., 2014a(Zhao et al., , 2014b, the pitch angle scattering loss (e.g., Hua et al., 2021;Summers et al., 2007;Zhu et al., 2021) and diffusive transports of energet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 73 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Following strong substorms (SME* > 400 nT), all of the L‐MLT bins with wave amplitudes of 10–30 pT are inside the plasmasphere. The average amplitude of the f > f lh magnetosonic waves is approximately five times smaller than that of the f < f lh magnetosonic waves (Kim & Shprits, 2018; Ma et al., 2019; Teng et al., 2019; Yan et al., 2021). The SME*‐dependence and MLT‐dependence of magnetosonic waves imply that they could be generated by westward drifting protons injected during substorms.…”
Section: Spatiotemporal Distribution Of F > Flh Magnetosonic Wavesmentioning
confidence: 96%
See 3 more Smart Citations
“…Following strong substorms (SME* > 400 nT), all of the L‐MLT bins with wave amplitudes of 10–30 pT are inside the plasmasphere. The average amplitude of the f > f lh magnetosonic waves is approximately five times smaller than that of the f < f lh magnetosonic waves (Kim & Shprits, 2018; Ma et al., 2019; Teng et al., 2019; Yan et al., 2021). The SME*‐dependence and MLT‐dependence of magnetosonic waves imply that they could be generated by westward drifting protons injected during substorms.…”
Section: Spatiotemporal Distribution Of F > Flh Magnetosonic Wavesmentioning
confidence: 96%
“…First, waves with sufficiently strong power spectral densities P B > 10 −8 nT 2 Hz −1 , large normal angles ψ > 75°, and high planarities F B > 0.7 are identified as candidate magnetosonic waves. These criteria are comparable to those used in previous magnetosonic wave statistics (Ma et al, 2019;Teng et al, 2019;Yan et al, 2021). Next, the candidate waves significantly deviating from the theoretical predictions are removed.…”
Section: Spatiotemporal Distribution Of F > F Lh Magnetosonic Wavesmentioning
confidence: 98%
See 2 more Smart Citations
“…Fung et al (2006) suggested that the most efficient wave-particle interactions occur off the magnetic equator in the slot region, however more recent studies investigating the individual wave modes responsible for the slot region have found varying results. Magnetosonic waves are typically located near the magnetic equator at |λ m | < 5° (e.g., Ma et al, 2013;Yan et al, 2021). Meredith et al (2018) found that the latitudinal distribution of plasmaspheric hiss intensity has two peaks: one at the magnetic equator and one at high magnetic latitudes (λ m ∼ 40°-50°) with a deep minimum in between.…”
Section: Example Decay Intervalmentioning
confidence: 99%